Creative entrepreneurs' creativity, opportunity recognition, and career success: Is resource availability a double-edged sword?. Issue 5 (October 2020) - Chang, Yu-Yu; Chen, Ming-Huei
Abstract: At the heart of the entrepreneurial process in creative industries are entrepreneurial creativity and opportunity recognition, which influence entrepreneurs' ability to create new ventures or significantly improve the position of an existing business. Recent entrepreneurship research has suggested that resource availability represents a double-edged sword, simultaneously facilitating and impeding new venture outcomes, while little research has explored how entrepreneurial creativity, opportunity recognition, and resource availability jointly affect entrepreneurial career success. To address the theoretical gap, this paper examines the moderating role of resource availability in the relationship between entrepreneurial creativity, opportunity recognition and career success of creative entrepreneurs. To reflect the career success perceived by business founders in creative industries, five indicators of entrepreneurial success are examined, including career achievement, social reputation, entrepreneurial happiness, capability enhancement, and financial satisfaction. Hierarchical regression analysis empirically examines a sample of 296 entrepreneurs in creative industries. Results suggest that entrepreneurial creativity and opportunity recognition are positively related to entrepreneurial career success. We also find that resource availability generally strengthens the effect of entrepreneurial creativity and opportunity recognition on entrepreneur-perceived career success. Nevertheless, the relationship between opportunity recognition and financial satisfaction is found to be weakened by entrepreneurs' resource availability. Integrating the theory of entrepreneurial effectuation and resource dependence theory, our findings indicate that entrepreneurial bricolage is crucial for creative entrepreneurship.